Sifat Gelatinisasi Beras Hitam Pratanak Varietas Sirampog pada Variasi Waktu Perendaman dan Konsentrasi Natrium Sitrat: Sifat Gelatinisasi Beras Hitam Pratanak Varietas Sirampog pada Variasi Waktu Perendaman dan Konsentrasi Natrium Sitrat - Nur Aini; Agung Widodo; Hidayah Dwiyanti (Universitas Bangka Belitung, 2022)
Black rice still contains epidermis which is composed of several layers, including pericarp, lemma, aleuron and testa so that cooking takes a long time. To speed up the cooking time on rice can be modified by parboiling process so that it changes the character of gelatinization. The research aims to find out the effect of the concentration of sodium citrate solution and immersion time on the process of black rice parboiled Sirampog varieties on its gelatinization properties. Soaking in sodium citrate solution at a certain time is expected to accelerate the cooking time of black rice. The research using Completely Randomized Factorial design consisting of concentration of sodium citrate solution (0, 3, 5 and 7%) and immersion time (20, 30 and 40 minutes). The variables observed were gelatinization properties including gelatinization temperature, peak viscosity, final viscosity, breakdown viscosity, trough viscosity and setback viscosity. The results showed that the setback viscosity and peak viscosity of Sirampog rice were affected by the concentration of sodium citrate. The sodium citrate solution of 5% as a marinade produces Sirampog varieties of parboiled rice with high trough viscosity and lowest setback viscosity, which means it is easier to cook and more resistant to retrogradation during cooling.